Physical and Functional Interaction between the Eukaryotic Orthologs of Prokaryotic Translation Initiation Factors IF1 and IF2 - Choi, Sang Ki (American Society for Microbiology, 2000)
To initiate protein synthesis, a ribosome with bound initiator methionyl-tRNA must be assembled at the start codon of an mRNA. This process requires the coordinated activities of three translation initiation factors (IF) in prokaryotes and at least 12 translation initiation factors in eukaryotes (eIF). The factors eIF1A and eIF5B from eukaryotes show extensive amino acid sequence similarity to the factors IF1 and IF2 from prokaryotes. By a combination of two-hybrid, coimmunoprecipitation, and in vitro binding assays eIF1A and eIF5B were found to interact directly, and the eIF1A binding site was mapped to the C-terminal region of eIF5B. This portion of eIF5B was found to be critical for growth in vivo and for translation in vitro. Overexpression of eIF1A exacerbated the slow-growth phenotype of yeast strains expressing C-terminally truncated eIF5B. These findings indicate that the physical interaction between the evolutionarily conserved factors eIF1A and eIF5B plays an important role in translation initiation, perhaps to direct or stabilize the binding of methionyl-tRNA to the ribosomal P site.